2003
DOI: 10.1118/1.1570372
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of patient deep inspiration self‐breath‐holding: How precisely can patients reproduce the tumor position in the absence of respiratory monitoring devices?

Abstract: The aim of the present study was to evaluate the reproducibility of tumor position under patient deep inspiration self-breath-holding in the absence of respiratory monitoring devices, as well as to compare the reproducibility of deep inspiration self-breath-holding on the verbal command of a radiation technologist (Passive mode) with that initiated by patients' own estimation (Active mode). Twenty patients with lung cancer were shown how the tumor and diaphragm move during the respiration cycle. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…Tumour motion can be unrestricted and monitored, with delivery of RT gated to a pre-defined phase of the respiratory cycle [13][14][15] or following the moving tumour [16]. Alternatively motion can be Brock 5 minimized by planning and treating in passive [17][18][19][20][21] or active [22,23] breathhold.…”
Section: Introductionmentioning
confidence: 99%
“…Tumour motion can be unrestricted and monitored, with delivery of RT gated to a pre-defined phase of the respiratory cycle [13][14][15] or following the moving tumour [16]. Alternatively motion can be Brock 5 minimized by planning and treating in passive [17][18][19][20][21] or active [22,23] breathhold.…”
Section: Introductionmentioning
confidence: 99%
“…Forth, we evaluated unidimensional measurements on the transaxial plane. Onishi and coworkers reported that tumors of lower or middle lung often demonstrated the largest respiratory movement along the craniocaudal axis and the smallest along the right-left axis [18]. Reproducible CT data for pulmonary nodules in the lung base must be obtained on coronal multiplanar reformatting plane to detect the largest respiratory movement.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the PTV mDIBH included an extra 3 mm margin from the GTV to account for the reproducibility of the tumor position during breath holding. The PTV FB required an extra 10 mm in the left-right and anterior-posterior directions, and an additional 15 mm in the cranio-caudal direction, to account for the uncertainty introduced by breathing motions during CT, while these margins may be unnecessarily large to ensure adequate PTV coverage (14,15). The mean PTV decreased by 50%, which significantly reduced the irradiated region in the normal lungs.…”
Section: Discussionmentioning
confidence: 99%
“…PTV mDIBH contained GTV mDIBH plus 8 mm margins in all directions. All margins contained the 5 mm distance between the GTV and PTV (15).…”
Section: Acquisition Of Gtvs and Ptvsmentioning
confidence: 99%